Penerapan Metode K-Means Clustering Terhadap Bencana Kebakaran Di Kota Samarinda - Wisnu Priyo Jatmiko; M. Gillang Ramadhani; M. Gilang Romadhon; Gilang Adhmadani; Rahmad Fardian; Wawan Joko Pranoto (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Fire is a disaster that cannot be predicted when it will occur and where it will occur, it's just that densely populated areas are areas that are vulnerable to the danger of fire. Fire disaster in Samarinda City. Data obtained from the Samarinda City Fire and Rescue Service are fire incidents from 2021 to 2023. In 2021 there were 230 fire incidents, in 2022 there were 209 fires, in 2023 there were 99 fires. so this city is one of the cities that experiences the most fires on the island of Kalimantan. Several supporting facilities and infrastructure owned by the Samarinda City Fire and Rescue Department, such as hydrants and fire extinguishing posts, have been increased in number. This research functions to group fire data per year using the k-means clustering algorithm.